Association of Pediatric Obstructive Sleep Apnea Severity with Sleep Endoscopy Findings: A Pilot Study. (2nd September 2014) - Lam, Derek J.; Weaver, Edward M.; O'Neill, Eleni I.; Milczuk, Henry A.; MacArthur, Carol J.; Shea, Steven A
Abstract : Objectives: (1) Determine the association of a sleep endoscopy rating scale with pediatric obstructive sleep apnea (OSA) severity. (2) Assess the reliability of this rating scale. Methods: This was a retrospective cohort study of pediatric patients who underwent drug‐induced sleep endoscopy (DISE) from January to December 2013 at a tertiary care children's hospital. DISE recordings were reviewed by 2 blinded senior pediatric otolaryngologists. Severity of obstruction was scored 0, 1, or 2 for no, partial, or complete obstruction at 6 levels: nasal airway, nasopharynx, velum, oropharynx, tongue base, and arytenoids. Ratings at each level were summed for a total score from 0‐12. Associations of DISE scores with obstructive apnea‐hypopnea index (OAHI) and OSA‐18 scores were assessed using linear regression. Interrater and intrarater reliability were calculated using a kappa statistic with linear weighting. Results: Twenty patients were included (mean age 8.4 ± 5.1 years, 55% obese, mean OAHI 16.5 ± 15.6). Associations between OAHI and DISE scores were strongest for the nasopharynx (beta = 12.3, P =. 09) and total score (beta = 4.7, P =. 06). Associations between OSA‐18 and DISE ratings were strongest for the nasopharynx (beta = 11.1, P =. 08) and velum (beta = 12.8, P =. 07). There was fair‐moderate interrater reliability (kappa 0.24‐0.63) and moderate‐almost perfect intrarater reliability (kappa 0.52‐0.88) at individual anatomic sites. Conclusions: Although observed associations did not reach statistical significance, this pilot study suggests clinically important associations between DISE ratings and OSA severity and showed promising interrater and intrarater reliability.